Improving new methods of growing high-quality potatoes in the Fergana region - Gulchehra Urunbaeva; X.Abdullaev (Zien Journals, 2022)
This article discusses the development of new methods of growing high-quality potatoes in the Fergana region, the study of technology and storage of vegetables in traditional and modern warehouses, the continuous supply of agricultural products is an important part of economic stabilization, various methods of storing vegetables described.
Keywords: modern warehouse; potato growing; agriculture; entrepreneurship